Analisis Strategi Pemasaran Syariah Dalam Meningkatkan Pembiayaan Aparatur Sipil Negara Di PT. Bank NTB Syariah Cabang Sriwijaya - Sani, Ahmad Rizqon; Mas'ud, Riduan; Sanurdi, Sanurdi; Amini, Titik Husnawati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research is motivated by the growth of ASN financing which is getting better from year to year amid banking competition in NTB requires Bank NTB Syariah to maintain growth and become the market leader in ASN financing. This research aims to analyze the marketing strategy at PT Bank NTB Syariah Sriwijaya Branch in increasing ASN financing and the factors that influence the increase in the number of customers in the financing. This is a descriptive qualitative research, with primary and secondary data sources. Secondary data is obtained from literature in the form of books, scientific papers, financial reports and other information. The data collection technique uses snowball sampling.The results of this study shows that the ASN consumer financing business has grown significantly, known from the increase in the number of customers and financing of Bank NTB Syariah Sriwijaya Branch. This is inseparable from the marketing strategy carried out by referring to the elements in the marketing mix, namely product, pricing, promotion, place, people, process, and physical evidence. There are several factors that influence it, such as cooperation between the bank and related agencies, services provided, marketing strategies that are in accordance with customer needs and desires, customer satisfaction with the features provided, and Word of Mouth